Genital ulcer disease in women in Durban, South Africa. Issue 4 (August 1991) - O'Farrell, N; Hoosen, A A; Coetzee, K D; van den Ende, J
Abstract : OBJECTIVE--To study the microbial aetiology of genital ulcer disease (GUD) in women. DESIGN--Microbial and clinical assessment of genital ulcers in women. SETTING--City Health sexually transmitted diseases clinic, King Edward VIII Hospital, Durban, South Africa. PARTICIPANTS--100 Zulu women with genital ulceration who had not received antibiotics in the previous two weeks. RESULTS--Syphilis was diagnosed in 40%, genital herpes in 18%, donovanosis (granuloma inguinale) in 16%, chancroid in 14%, lymphogranuloma venereum in 7% and scabies in 2%. No recognised cause was detected in 18%. Secondary syphilis was diagnosed in 21%, primary syphilis in 16% and mixed primary and secondary syphilis in 3%. Multiple infections were detected in 13 women, of whom 12 had syphilis. Bleeding was observed from the ulcers of 59 during swab collection. Three women had HIV-1 antibodies. Neisseria gonorrhoeae was isolated from the ulcers and endocervix of two women and from the endocervix alone in nine. Generalised scabies was diagnosed in 14. CONCLUSIONS--All the major causes of GUD are prevalent in Zulu women in Durban: secondary syphilis was the commonest diagnosis. Donovanosis, which often presents late with large ulcers, and genital herpes are now significant problems. Mixed infections with coexisting syphilis are common. All women in this population with GUD should be treated for syphilis and receive oral antibiotics effective for chancroid and donovanosis.